Last chance Harvey - Hopkins, Joel, 1970-; Hoffman, Dustin, 1937-; Thompson, Emma; Baker, Kathy, 1950- (Burbank, CA : Anchor Bay Entertainment, 2009)
Rejected by his family at his daughter's London wedding, an aging jingle writer connects with a lonely civil servant who has a smothering mother.
Originally released as a motion picture in 2008.
Features: audio commentary; An unconventional love story : the making of "Last chance Harvey."
Dustin Hoffman, Emma Thompson, Kathy Baker, James Brolin, Eileen Atkins, Richard Schiff, Liane Balaban.
MPAA rating: PG-13.
DVD, Dolby digital.
Keywords: Man-woman relationships -- Drama; Dysfunctional families -- Drama; Middle-aged persons -- Drama; Romance films; Fiction films; Feature films